ANALISIS IMPLEMENTASI KEBIJAKAN TATA RUANG DI KOTA YOGYAKARTA - Nahak, Theresia Wilmince; Diah Utami Lutfiani; Caecilia Putri Gennosa; Muhammad Zahidi; Virgiawan Rambu Rabana; Suyatno (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Yogyakarta City faces significant challenges due to rapid population growth and rapid urban expansion. This has resulted in high density in various areas, triggering various social and environmental problems. Declining air quality, limited green open spaces, and pressure on infrastructure are key issues that need to be addressed immediately. This research method uses a qualitative descriptive approach to explore how spatial planning policies are implemented by the Yogyakarta City Government. The results show that the implementation of spatial planning policies in Yogyakarta City is marked by challenges such as uncontrolled spatial planning, inadequate land management, and the need for stricter law enforcement against spatial planning violations. Community participation in the planning and decision-making process has proven to be important in strengthening the sustainability of these policies. This study provides important insights into how spatial planning policies can be implemented effectively in the context of a rapidly growing city. The implications of this study emphasize the importance of sustainable and participatory spatial planning policies to maintain a balance between economic development, social needs, and environmental conservation in Yogyakarta City.